Determinación de la pena proporcional en el delito de robo agravado en las fiscalías penales de Maynas periodo 2021 – 2022 - Aspajo Reyna, Lucía Fariza (2025)
This research work addresses as a general problem whether, in proceedings for the crime of aggravated robbery, the Criminal Prosecutors of Maynas, during the period 2021 - 2022, individualize the specific sentence over the imposed sentence for the crime of simple robbery, in accordance with the principle of proportionality developed in the judgment of file No. 00413-2021 PHC / TC (2021). The general objective is to determine whether, in such proceedings, the accusations were formulated by said Criminal Prosecutors' Offices in accordance with the constitutional pronouncement, in order to determine the sentence for the crime of aggravated robbery, based on the imposed sentence corresponding to the crime of simple robbery, in order to guarantee the principle of proportionality. The research was of an applied type, because it sought means to help solve a problem, focused on a current situation and specific context; the methodological approach was quantitative, considering that the proof of the hypothesis required the measurement and descriptive statistics of the variables; The research was correlational in nature, as information was collected and the link between the study variables was determined. The hypothetical-deductive method was used because a response to the problem posed was postulated in advance by formulating hypotheses that were accepted as true. It has been determined that, during the 2021-2022 period, the Maynas Criminal Prosecutor's Office filed charges for the crime of aggravated robbery, and the specific sentence was determined based on the imposed sentence for said crime. This disregarded the principle of proportionality developed by the Constitutional Court in the ruling issued in file no. 00413-2021-PHC/TC (2021).